Proceedings of the 46th ACM Technical Symposium on Computer Science Education 2015
DOI: 10.1145/2676723.2677253
|View full text |Cite
|
Sign up to set email alerts
|

Generating Practice Questions as a Preparation Strategy for Introductory Programming Exams

Abstract: Written exams are a common form of assessment in introductory programming courses. Creating exam questions is normally the responsibility of the course instructor, however the process of authoring such questions may be a useful learning activity in itself. We explored this idea with a randomized controlled experiment (n > 700) in which a group of first-year programming students generated practice questions prior to an exam. Even though all questions were available to every student in the course for practice, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A common use of question repositories in PeerWise by students is for review and practice purposes leading up to summative tests and exams. Prior work has shown that answering activity in PeerWise typically increases rapidly before a test [38], and that answering questions is strongly predictive of subsequent test performance [39], [40]. Instructors are also able to make use of the questions, for example by reviewing a question repository to identify topics that are challenging for students, or by selecting high-quality questions for use on summative tests and exams.…”
Section: Crowdsourcing Systems a Peerwisementioning
confidence: 99%
“…A common use of question repositories in PeerWise by students is for review and practice purposes leading up to summative tests and exams. Prior work has shown that answering activity in PeerWise typically increases rapidly before a test [38], and that answering questions is strongly predictive of subsequent test performance [39], [40]. Instructors are also able to make use of the questions, for example by reviewing a question repository to identify topics that are challenging for students, or by selecting high-quality questions for use on summative tests and exams.…”
Section: Crowdsourcing Systems a Peerwisementioning
confidence: 99%
“…Collaborative question generation improves self-confidence and critical thinking, sheds light on different ways to solve a problem, supports ideation, exhilarates students, facilitates rapid peer-evaluation, and improves deep learning [64,19,76,25,16,65,14,6,27,47,45,4,8,17,60,49,22]. Creating question stems, correct/wrong choices, and justifications for each choice involves critical thinking and evaluation that result in deep learning [25,49,20].…”
Section: Collaborative Question Generationmentioning
confidence: 99%
“…This motivation typically declines over time [33,31]. Different studies have incentivized students' contributions through course grades or paying them as subjects of the study [76,14,25,29,20,49,38]. Gamification, through a serious board game, is also proposed [77].…”
Section: Motivation In Collaborative Learningmentioning
confidence: 99%
“…Gamification is the application of game-design elements principles in non-game contexts (De-Marcos, et al 2014;Robson, et al 2015;Nehring et al 2018). It employs game design elements to achieve different goals including improving user engagement (Hamari, 2015;Nehring et al 2018), user behaviour (Reddy, 2018), organizational productivity (Zichermann & Cunningham, 2011) and learning (Denny, 2015;Gooch et al, 2016;Cózar-Gutiérrez, et al 2016). Gamification has been shown to increase learners' engagement with course materials and improve their motivation, learning participation and collaboration (Denny, 2015;Dicheva et al 2015;Nehring et al 2018).…”
Section: Introductionmentioning
confidence: 99%